Desenvolvimento e caracterização de indicador de tempo-temperatura a partir de quitosana, PVA e antocianinas para aplicações em embalagens inteligentes - Pereira Junior, Valdir Aniceto (2014)
Food packages featuring time-temperature indicators are considered intelligent packages, due to the use of a system that monitors the food conditions in real time. Time-Temperature indicators or integrators (TTIs) are defined as simple, effective and easy to use devices for monitoring, recording and cumulatively indicate the overall influence of temperature history on the quality of the food product, from manufacturing to the end consumer. Thus, this study aimed to develop and characterize a Time-Temperature indicator sensor based on a polymer blend of PVA and chitosan doped with anthocyanins to establish the variations of time-temperature indirectly from the changes of pH in food products, when subjected to improper storage temperatures. The TTI are produced from chitosan and PVA, as well as anthocyanins extracted from Brassica oleracea var. capitata, from the Brassicaceae family (red-cabbage). The TG-DSC, FT-IR, UV-Vis techniques were used to characterize the TTI, as well as swelling index (Si), and definition of the total variation of color through CIELab scale, after activation at different pH (1,0 to 12,0). Tensile (stress/strain) test was made in order to establish the mechanical properties of TTI. The results from TG-DSC curves and IR spectra indicated that there was a physical interaction, not a chemical one, between PVA and chitosan in film formation. Visually, the TTI showed translucency, being characterized by the purple color from anthocyanins in neutral pH. The value found for the swelling index (38,02±0,03%) is due to the high concentration of PVA in the constitution of TTI. The results for the activation color change test were excellent, considering that changes color in different pH TTI, which was corroborated by the application test in pasteurized milk. In relation to the mechanical tests, the results characterizes the TTI for packaging applications. Therefore, it is concluded that it is possible to use the TTI the basis of chitosan and PVA anthocyanins sensor indicator variations of time and temperature to form an intelligent food packaging, whereas when foods are kept at inappropriate temperatures, cooling starts the process of deterioration, which most often results in changes in pH, being the key to activating the TTI this parameter.